2020
DOI: 10.1021/acsaem.0c02299
|View full text |Cite
|
Sign up to set email alerts
|

Na2MoO4-Incorporated Polymer Gel Electrolyte for High Energy Density Flexible Supercapacitor

Abstract: The recent advancement in flexible/bendable displays such as phones, smart bands, laptops, and televisions demands flexible energy storage devices. Heteroatom-doped graphene electrodes are promising candidates for flexible energystorage applications because of its dual nature of electrochemical double-layer capacitance and pseudocapacitance. The low energy density of supercapacitors limits their potential use and attempts are in progress to overcome this issue. Redox-additive electrolytes are presumed to be on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…The deconvoluted C 1s high-resolution spectrum (Figure A) reveals the presence of four well-defined peaks at 284.5, 285.7, 287.6, and 290.3 eV, attributed to the nonoxygenated sp 2 carbon, sp 3 carbon, C–N, and CO bonds, respectively . Similarly, the three peaks at 284.4, 285.4, and 287.4 eV observed for the deconvoluted N 1s spectrum attributed to the presence of pyridinic-N, pyrrolic-N, and quaternary/graphitic-N, respectively (Figure B). The intensity of pyrrolic-N is more than the other peaks. Moreover, the amount of N present in the PW-700 has also been quantified using XPS.…”
Section: Results and Discussionmentioning
confidence: 85%
“…The deconvoluted C 1s high-resolution spectrum (Figure A) reveals the presence of four well-defined peaks at 284.5, 285.7, 287.6, and 290.3 eV, attributed to the nonoxygenated sp 2 carbon, sp 3 carbon, C–N, and CO bonds, respectively . Similarly, the three peaks at 284.4, 285.4, and 287.4 eV observed for the deconvoluted N 1s spectrum attributed to the presence of pyridinic-N, pyrrolic-N, and quaternary/graphitic-N, respectively (Figure B). The intensity of pyrrolic-N is more than the other peaks. Moreover, the amount of N present in the PW-700 has also been quantified using XPS.…”
Section: Results and Discussionmentioning
confidence: 85%
“…Liu et al reported that double-cross-linked HEs possessed excellent stability and a great tensile strength up to 3.1 MPa . However, the solid-state DN HEs still possess inferior energy densities. , The supercapacitors with redox electrolytes, such as KI and Na 2 MoO 4 , have been proved to possess much-enlarged capacitance and increased energy density. , To address the small capacitance and low energy density of supercapacitors, we introduce Na 2 MoO 4 , a kind of pseudocapacitive redox additive, into the double-network gel electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29]31 The supercapacitors with redox electrolytes, such as KI and Na 2 MoO 4 , have been proved to possess much-enlarged capacitance and increased energy density. 32,33 To address the small capacitance and low energy density of supercapacitors, we introduce Na 2 MoO 4 , a kind of pseudocapacitive redox additive, into the double-network gel electrolytes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…While they have good mechanical properties and are very suited to flexible devices, the solid electrolytes typically show low ionic conductivity and overall performance. Gel polymer electrolytes (GE) are a great compromise between Molecules 2021, 26, 2631 2 of 12 the liquid and solid, have relatively good mechanical properties, are lightweight, can be packaged easily, and can have higher ionic conductivity than the solids [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%